2022
DOI: 10.1590/fst.29022
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antioxidant activity of date (Phoenix dactylifera L.) varieties at various maturity stages

Abstract: The current study was conducted to determine the effect of four maturity stages on the chemical composition and antioxidant activity of date (Phoenix dactylifera L.) varieties. Four varieties of date palm viz., Zahidi, Aseel, Halawi, and Dhaki were used at four ripening stages (Kimri, Khalal, Rutab, and Tamer). The protein and fat contents of all the selected varieties of dates decreased from Kimri to the tamer stage of development. In all the date varieties the glucose, fructose, and total sugar contents were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In addition, a similar study used RapidOxy to monitor the accelerated oxidative stability of sunflower oil, which decreased with each refining step since the crude oil was more stable than the refined one, indicating that it lost antioxidant molecules during this process (Rhazi et al, 2022). Bano et al (2022) demonstrated that date varieties at various maturity stages had an important antioxidant activity (Bano et al, 2022). Therefore, it is necessary to add antioxidants, preferably natural ones, to the refined oils used for frying.…”
Section: Preliminary Accelerated Oxidation Test: Rapidoxymentioning
confidence: 99%
“…In addition, a similar study used RapidOxy to monitor the accelerated oxidative stability of sunflower oil, which decreased with each refining step since the crude oil was more stable than the refined one, indicating that it lost antioxidant molecules during this process (Rhazi et al, 2022). Bano et al (2022) demonstrated that date varieties at various maturity stages had an important antioxidant activity (Bano et al, 2022). Therefore, it is necessary to add antioxidants, preferably natural ones, to the refined oils used for frying.…”
Section: Preliminary Accelerated Oxidation Test: Rapidoxymentioning
confidence: 99%
“…Several research studies strongly confirm high dietary fiber content in dates, showing that date products are a better source of dietary fiber than some cereal products such as rice and oats, and could be incorporated as an ingredient in fiber-enriched food [10,59,60]. The obtained data were higher than those reported by Bano et al [61], oscillating between 5.48 to 9.83% for TDF, between 3.43 to 3.59% for SDF, and between 5.98 to 6.24% for IDF, while being lower than those recorded by Hashim and Khalil [54] ranging from 50.81 to 56.52% for TDF, from 6.19 to 9.15% for SDF, and from 41.66 to 49.99% for IDF.…”
Section: Characterization Of Dietary Fiber Compositionmentioning
confidence: 79%
“…The increased levels of glucose and fructose could be linked to the activity of the invertase enzyme, responsible for converting sucrose into glucose and fructose, a process that usually intensifies as the fruit ripens [ 69 ]. Variations in sugar concentration are likely to be influenced by environmental and genetic factors, impacting both the qualitative and quantitative composition of the sugar fraction through their effects on enzyme activity involved in synthesis, breakdown processes, and fruit maturation [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a massive amount of the harvest is wasted, mainly due to over ripeness of product, poor handling during processing, disruption of the storage, packaging and marketing process. [3], reported that 60 000 tons of dates are lost every year in Algeria, representing a real economic loss, as they are rich in noble components, including a large part of sugars in addition to dietary fiber, phenolic compounds, minerals, vitamins and antioxidant compounds [4][5][6].…”
Section: Introductionmentioning
confidence: 99%